The Relationship Between the Implementation of the Legislative Function of the DPRD with the Optimization of the Principles of Good Governance in The North Gorontalo District Government - Herry Pasrani Mendrofa; Poltak Siringoringo; Fernando Silalahi (Dinasti Research, 2025)
The Regional People's Representative Council (DPRD) has an important role in forming local regulations (Perda) that reflect the needs of the community. However, in North Gorontalo Regency, the number of draft local regulations has decreased due to sectoral ego, lack of political communication with the local government, and limited derivative regulations from the center. Therefore, this study aims to analyze the relationship and influence of the implementation of DPRD's legislative function on the implementation of good governance principles in North Gorontalo District Government. This research uses quantitative methods with a population of 130,400 people and a sample of 400 respondents selected through probability sampling techniques. Data were analyzed using Jeffrey's Amazing Statistics Program (JASP) application. The results showed that there is a significant relationship between the implementation of DPRD's legislative function and the optimization of good governance in North Gorontalo Regency. DPRDs play a strategic role in ensuring that governance runs in accordance with the principles of democracy, transparency, accountability, effectiveness and efficiency. In addition, the influence of DPRD's legislative function can also be seen in efforts to improve the quality and quantity of legislative products to meet the priority needs of the community. Therefore, synergy between DPRDs and local governments needs to be improved through better political communication to reduce sectoral egos and ensure the implementation of good governance.